1985
DOI: 10.1227/00006123-198502000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Traumatic Abducens Nerve Palsy without Skull Fracture and with Cervical Soine Fracture: Case Report and Review of the Literature

Abstract: Bilateral traumatic abducens nerve palsy is a rare condition. Here a case without skull fracture and associated with cervical spine fracture is reported. Only two cases like this were found in a review of the literature. The mechanism of the lesion is discussed in light of the two main theories proposed thus far. When the injury is acute, as happens in the majority of cases, the nerve lesion probably is due to contusion and stretch of the nerve trunk against the ridge of the petrous bone and the rigid dural ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The incidence of cranial nerve injury following closed head injury varies between 5% and 23% ( Pathi et al 2021 ), while the reported incidence of unilateral abducens palsy from head trauma is 1–2.7% ( Arias 1985 ). In the current case report, we highlight the role of high-resolution imaging in such orbital and head trauma.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of cranial nerve injury following closed head injury varies between 5% and 23% ( Pathi et al 2021 ), while the reported incidence of unilateral abducens palsy from head trauma is 1–2.7% ( Arias 1985 ). In the current case report, we highlight the role of high-resolution imaging in such orbital and head trauma.…”
Section: Discussionmentioning
confidence: 99%
“…1) Traumatic injuries of abducens nerve as a consequence of severe facial and/or head trauma have been observed in the presence or absence of associated cervical or skull base fracture. While the reported incidence of unilateral abducens palsy from head trauma is 1–2.7%, 2) unilateral avulsion of the abducens nerve has not been documented. Advances in magnetic resonance imaging (MRI) have made it possible to detect the abducens nerve.…”
Section: Introductionmentioning
confidence: 98%
“…First, several authors have highlighted the angulations of the course of the abducens nerve through the skull base as a reason for predisposition to injury under specific pathological conditions ( Iaconetta et al, 2001 , 2003 , 2007 ). The marked bending of the abducens nerve at the level of the petrous apex, at an angle of approximately 90°, is particularly emphasized in explaining its vulnerability ( Wolff, 1928 ; Arias, 1985 ; Umansky et al, 1991 , 1992 ; Tekdemir et al, 1996 ; Ozveren et al, 2002a ; Ozer et al, 2010 ; Joo et al, 2012 ; Azarmina and Azarmina, 2013 ). Other points of bending along the abducens pathway are also mentioned, e.g., the angulation between the cisternal part and the point where the abducens nerve first becomes extradural, and lateral bend in its course as it leaves Dorello’s canal and enters the cavernous sinus ( Iaconetta et al, 2001 ).…”
Section: Introduction and Aimsmentioning
confidence: 99%
“…As described by Wolff (1928) , “the weakling of the cranial contents, the sixth nerve may be affected in almost any type of cerebral lesion. It is thus notorious, if involved alone, for having no localizing value.” According to traditional teaching in neurology, the susceptibility of the abducens nerve is attributed to its long intracranial course ( Sachsenweger, 1969 ; Arias, 1985 ; Umansky et al, 1992 ; Ten Donkelaar, 2011 ; Joo et al, 2012 ; Standring, 2021 ). However, the trochlear nerve, which exits through the dorsal aspect of the midbrain and thus has a longer course through the cranial base, is rarely injured in patients with increased intracranial pressure ( Joo et al, 2012 ).…”
Section: Introduction and Aimsmentioning
confidence: 99%